Separating Interleaved Notebooks - Elliott Nelson (International Scholastic Journal of Science, 2024)
It is well known that bound books with interleaved pages can be difficult to separate because of frictional forces. In this work a theoretical model is developed for a special case: the force required to separate horizontally oriented spiral bound notebooks. It is found that the relationship between the mimimum separation force and the number of interleaved pages closely follows the theoretical model.